Performance Analysis of Cooperative Hybrid Cognitive Radio Network with Various Diversity Techniques - C.S. Preetham; M.S.G. Prasad; D.S.S.L. Saranya; Charan Teja Somepalli; D. Bhargava Satya Sai Krishna; V. Rohit (International Journal of Electrical and Computer Engineering (IJECE), 2016)
The extensive growth in wireless communications leads to spectrum scarcity. Since the spectrum is limited spectrum usage is clogged. The best possible solution is usage of cognitive radio. A cognitive radio network with sender, receiver and intermediate devices as relays is analyzed. The channel is modelled with noise considerations, path loss and variance. The system is defined with one primary sender and one primary receiver, in between them five secondary users and two active users. The signals from all these paths are estimated and analyzed to draw the best signal with good signal to noise ratio (SNR). To improve the channel efficiency and quality, we have considered various diversity techniques for which the fading problem of channel can be eliminated. In view of this, we concentrated on improving the system performance with various diversity techniques and optimum weight adaptation concept.